Methodische Fortschritte der wissenschaftlichen Luftbild-Interpretation (2): Fortsetzung des Berichts aus Erdkunde 1958/2, S. 81-107 - Schmidt-Kraepelin, Ernst (ERDKUNDE, 1959)
The improved standard of instruments, the general ways of interpretation, and the geological application of aerial photographs have been dealt with in the last number of this publication (Erdkunde, 2, 1958, p. 81 — 107). Here, the geomorphological interpretation of aerial photographs is discussed, and their importance foe both scientific and practical purposes demonstrated. The tasks of regional study, regional planning, and cartography are seen first of all from the point of view of co-operation between geodesy and geography, which seems essential for the photogrammetrical interpretation of small scale aerial photographs, and for the adaptation of morphological maps. Special attention is paid to the morphological, regional, and bibliographical work that has been carried out in Germany within the last 15 years. Examples of the work done abroad show the necessity of a close co-operation between aerial photography and geography. The index is arranged according to subjects, and supplements the index given in the previous paper (Erdkunde, 2, 1958).